Users’ Acceptance of Kumandang Interactive Reading Aloud Smartphone-Based Apps - Ni Komang Dwi Eka Yuliati; Made Hery Santosa; Setya Chendra Wibawa (Universitas Pendidikan Ganesha, 2022)
In 21st century learning, the development of smartphone-based applications to support education, especially literacy, has become a basic need. This study aims to analyze the factors that factor in user acceptance of an Android-based application called Kumandang, Reading Aloud Activities. This type of research is survey research. The subjects of this study were ninety participants consisting of teachers, parents, and guardians. The research instrument used in this study was a questionnaire sheet. The technique of data collection is the distribution of questionnaires. The data analysis technique uses a structural equation model with the help of the SMARTPLS application. The study model uses UTAUT2, which consists of several indicators, including; Performance Expectations (PE), Business Expectations (EE), Social Influence (SI), Facilitation Conditions (FC), Price Value (PV), Hedonic Motivation (HM), and Habits of Behavioral Intentions (H). The results showed that business expectations (EE) related to the ease and convenience of using Kumandang positively affected user acceptance. In addition, hedonic motivation (HM) related to fun and entertainment also affects parents' intention to use the Kumandang application. The results also show that performance expectations (PE), social influences (SI), facilitating conditions (FC), habits (H), and price effects (PV) do not affect parents' acceptance of using the Kumandang application.